Outbreak of human astrovirus 1 lineage 1d in a childcare center in China - Hou, Meiling; Liang, Xuexue; Tan, Liqian; Liu, Pengfei; Zhao, Wei (Virologica Sinica, 2016)
Dear Editor,Astrovirus is an enteric virus associated with sporadic diarrhea or large outbreaks of gastroenteritis（Mendez et al.,2013）.Until 2008,human astroviruses（HAst Vs）were classified into eight serotypes—HAstV-1 to HAstV-8—based on the reactivity of their capsid protein with type-specific antibodies.Among these serotypes,HAstV-1is the most prevalent globally.However,some divergent new astroviruses（MLB1/MLB2,VA1/VA2/VA3,